OPTICS OF LOOKING TO THE FUTURE (Paper 3) - V. I. Baidenko; N. A. Selezneva (Высшее образование в России, 2018)
Keeping with the topics of 9th-11th European Quality Assurance Forums (EQAF), the paper analyzes the impact that a new pedagogical paradigm has on changes in higher education as well as on developing a new quality assurance methodology. At present Europe is featured by a new inter-university institution – tutor support of students; developing assessment practices for professionally-oriented baccalaureate and changes of state policy tools in higher education due to the advent of a new public management. The authors monitor a practice of surveying students and graduates and present results of t4SCL project aimed at developing sustainable strategies and methods of student-centered learning. The paper identifies the focus of 10th and 11th EQAF on trends in higher education development for the coming decades and reveals the dynamics of mentality changes in higher education occurred for the time of the Forums.